Gestión del talento y rendimiento laboral en la Gerencia Sub Regional de Ucayali Contamana 2025 - Abisrror Vasquez, Huber Manuel (2026)
The purpose of this study was to determine the relationship between talent management and work performance in the GSRU - Contamana, 2025. The research was of a basic type, with a quantitative approach, descriptive correlational level and a non-experimental cross-sectional design. The population and sample consisted of 89 administrative servants, applying two questionnaires validated by expert judgment and with a reliability of α = 0.915 for both variables. The descriptive results revealed that 40% of the staff rated talent management as fair and 23% as deficient, evidencing limitations in the planning, training and evaluation of personnel. In terms of work performance, 40% of those surveyed had a medium level and 20% a low level, which indicates deficiencies in motivation and productivity. It is concluded that, using Pearson's coefficient (r = 0.947; p = 0.000) it confirmed a positive and significant correlation between both variables, demonstrating that adequate talent management directly influences the improvement of personnel performance.